Pressure sensor, glass wafer and manufacturing method
Patent Information
- Application Number
- JP2023555410
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-10
- Filing Date
- 2022-03-10
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2042-03-10
AI Technical Summary
Existing pressure sensors face challenges in achieving high measurement accuracy due to variations in thickness, cavities, cracks, and other defects in thin glass articles, which affect thermal decoupling and adhesion, leading to non-uniform thermal decoupling and reduced performance.
The development of glass articles with specific manufacturing processes that minimize thickness variations and surface damage, such as controlling vibration frequencies during drawing and optimizing viscosity profiles, to ensure uniform thermal decoupling and improved adhesion in pressure sensors.
The solution results in glass articles with reduced near-surface damage and position-thickness variations, enhancing measurement accuracy and thermal decoupling, thereby improving the performance of pressure sensors.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass article and its use in a pressure sensor. The present invention also relates to a method for producing said glass article. [Background technology]
[0002] In the process of increasing digitalization, the use of intelligent and networked systems that rely on sensor data is increasing. Improved analysis methods, for example using artificial intelligence, allow the evaluation of large amounts of data and open up the possibility of using even small changes in measured values for automation and control. To further this development, increasingly accurate sensors are desired. An example of such a sensor is the pressure sensor.
[0003] Pressure sensors are used in many fields, in particular for controlling machines and industrial plants, for example in the food production or petrochemical industry, and also in the automotive field, for example for measuring oil and tire pressure.
[0004] A microelectromechanical (or MEMS) pressure sensor comprises a thin film made of silicon that can be elastically deformed by pressure. This silicon membrane is usually mounted on a base made of an insulating or semiconducting material, for example silicon. The base comprises an opening through which a fluid, for example a gas, can enter the measurement cavity of the pressure sensor. Here, pressure acts on the membrane from both sides, with a defined or variable reference pressure acting on one side as well as a variable pressure acting on the side of the membrane facing the measurement cavity. There are also sensors that work without a reference pressure, i.e. the reference pressure can be variable. If the pressures on both sides of the membrane differ from each other, the membrane is deformed. Measuring resistors are integrated into the membrane, which change their resistance when deformed (so-called piezoresistive resistors). Electrically they are arranged in the form of a so-called Wheatstone bridge circuit. The deformation of the membrane leads to a change in the voltage of the bridge circuit. This measurable change in the bridge voltage is approximately proportional to the pressure difference.
[0005] Glass articles are suitable as components for pressure sensors. An exemplary structure of such a pressure sensor is shown in Figure 1. The membrane is deformed in response to the applied pressure. The deformation, and therefore the pressure, is measured via the change in resistance of a piezoresistive element in the membrane. Summary of the Invention [Problem to be solved by the invention]
[0006] Pressure sensors with better measurement accuracy are desired. [Means for solving the problem]
[0007] Description of the invention In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 The average near-surface damage level (ONSL) at 2 the glass article having an average position-thickness variation (ODS) normalized to thickness at less than 10 nm per micrometer of thickness, said ODS being the difference between the highest and lowest thickness within a defined measurement area.
[0008] The glass article of the invention is suitable for use as a component in a pressure sensor. One function of such a glass component is to thermally isolate the membrane used for the measurement from the base material and the environment. The more accurate the desired measurement, the more important is a good, fast and above all uniform thermal isolation. Pressure sensors also tend towards miniaturization. Components are becoming smaller and smaller and thinner. One advantage of glass is that it can be manufactured with good surface quality, especially at low thicknesses. However, as pressure sensors become smaller overall, the impact of even small deviations becomes greater. Even the effect of certain vibration frequencies on glass during forming, for example in the downdraw process, can lead to thickness variations over small areas, which contribute to local deviations in heat transfer.
[0009] In handling and post-processing of glass articles, such as polishing, grinding, lapping, small damage can be introduced into the glass that penetrates surprisingly deeply. Due to the very small thickness of the glass articles used in pressure sensors, cracks of a few micrometers deep can already significantly affect the properties of the glass article, including heat transfer.
[0010] Thickness variations, cavities, cracks, and similar defects can impair the connection between the glass article and other components of the pressure sensor. For example, it may be more difficult to attach the components together, or more adhesive may be required to compensate for the irregularities or cracks. The use of additional adhesives or inorganic frits can impair the uniformity of the thermal decoupling.
[0011] The provision of the glass article according to the invention can be achieved, for example, if certain measures are taken in the shaping and optional surface treatment of the glass. For example, it has proven beneficial if during the drawing process a certain area is kept free of vibrations in the frequency range 0.01-500 Hz, for example 0.05-400 Hz, 0.1-300 Hz, 0.5-250 Hz, 0.8-200 Hz, 1-100 Hz, 4-75 Hz, or 5-50 Hz. Preferably, during the drawing process a certain area is kept free of vibrations having a frequency of at least 0.01 Hz, at least 0.05 Hz, at least 0.1 Hz, at least 0.5 Hz, at least 0.8 Hz, at least 1 Hz, at least 4 Hz, or at least 5 Hz. Preferably, during the drawing process, certain areas are kept free of vibrations having frequencies of up to 500 Hz, up to 400 Hz, up to 300 Hz, up to 250 Hz, up to 200 Hz, up to 100 Hz, up to 75 Hz, or up to 50 Hz. In surface treatment, it may be reasonable to follow certain parameters described within this application regarding the particle size used.
[0012] In one aspect, the present invention relates to the use of the glass articles described herein as components in a pressure sensor, for example, the glass articles can be used for components serving for thermal decoupling of a measurement membrane.
[0013] Said glass article can be used for pressure sensors which allow higher measurement accuracy. For use in pressure sensors the glass article can be perforated. This solution is based on the idea that for high measurement accuracy the thermal decoupling of the silicon membrane of the pressure sensor from the medium to be measured should be as uniform as possible. For uniform thermal decoupling it turns out that variable position-thickness variations (ODS) and near-surface damage levels (ONSL) are important. By suitable measures in manufacturing such glass articles can be obtained.
[0014] In one embodiment, the present invention is a method for manufacturing a glass article, comprising the steps of: producing a glass melt, - fining the glass melt; drawing the glass melt, in particular using drawing rolls, into a glass ribbon having a target thickness in the range of less than 3.0 mm, dividing the glass ribbon into glass articles. the glass ribbon passes through a region Z, where the glass ribbon exceeds a target thickness by less than 10%, but its viscosity is still less than 10 10 is less than dPas, the glass is drawn in the zone Z at a drawing speed of at least 0.5 m / min and at most 50 m / min, for example 2 to 10 m / min, 10 to 25 m / min, or 25 to 50 m / min; and wherein appropriate measures are taken to keep the region Z free from interference effects in the frequency range of 0.01-500 Hz, e.g. 0.05-400 Hz, 0.1-300 Hz, 0.5-250 Hz, 0.8-200 Hz, 1-100 Hz, 4-75 Hz, or 5-50 Hz.
[0015] The glass may for example be drawn at a drawing speed of at least 0.5 m / min, at least 2 m / min, at least 10 m / min, or at least 25 m / min in zone Z. It may for example be drawn at a drawing speed of up to 50 m / min, up to 25 m / min, or up to 10 m / min in zone Z.
[0016] For example, suitable measures may be taken to keep region Z free from interference having a frequency of at least 0.01 Hz, at least 0.05 Hz, at least 0.1 Hz, at least 0.5 Hz, at least 0.8 Hz, at least 1 Hz, at least 4 Hz, or at least 5 Hz. For example, suitable measures may be taken to keep region Z free from interference having a frequency of up to 500 Hz, up to 400 Hz, up to 300 Hz, up to 250 Hz, up to 200 Hz, up to 100 Hz, up to 75 Hz, or up to 50 Hz.
[0017] In particular, it has been found that frequencies above 1 Hz are associated with the appearance of relevant position-thickness variations. Therefore, suitable measures should be taken to keep the area Z free from interference effects in the frequency ranges 1-500 Hz, 2-400 Hz, 3-300 Hz, 4-250 Hz, 5-200 Hz, 10-100 Hz, 15-75 Hz, or 20-50 Hz. For example, suitable measures may be taken to keep the area Z free from interference effects having frequencies of at least 1 Hz, at least 2 Hz, at least 3 Hz, at least 4 Hz, at least 5 Hz, at least 10 Hz, at least 15 Hz, or at least 20 Hz. For example, suitable measures may be taken to keep the area Z free from interference effects having frequencies of up to 500 Hz, up to 400 Hz, up to 300 Hz, up to 250 Hz, up to 200 Hz, up to 100 Hz, up to 75 Hz, or up to 50 Hz.
[0018] The drawing of the glass melt may include, inter alia, downdraw or overflow fusion. In both cases, the glass melt emerges from the bath and is then drawn into a glass ribbon. The viscosity that the glass melt has at the point where it emerges from the bath is relevant for the appearance of position and thickness variations. In particular, the viscosity must not be too high for the glass melt to be properly drawn. However, if the viscosity is too low, the glass ribbon will be too long in the viscosity range that makes it prone to position and thickness variations during drawing. Therefore, the viscosity of the glass melt as it emerges from the bath should be within the range of 10 2.20 dPas or more, 10 2.30 dPas or more, 10 2.40 dPas or more, 10 2.50 dPas or more, 10 2.60 dPas or more, 10 2.70 dPas or more, 10 2.80 dPas or more, 10 2.90 dPas or more, 10 3.00 dPas or more, 10 3.10 dPas or more, 10 3.20 dPas or more, or 10 3.30 The viscosity of the glass melt as it leaves the bath should be, for example, up to 10 4.00 dPas, up to 10 3.90 dPas, up to 10 3.80 dPas, up to 10 3.70 dPas, up to 10 3.60 dPas, or up to 10 3.50 The viscosity of the glass melt as it leaves the vessel may be, for example, 10 2.20 dPas~10 4.00 dPas, 10 2.30 dPas~10 4.00 dPas, 10 2.40 dPas~10 3.90 dPas, 10 2.50 dPas~10 3.90 dPas, 10 2.60 dPas~10 3.80 dPas, 10 2.70 dPas~10 3.80 dPas, 10 2.80 dPas~10 3.70 dPas, 102.90 dPas~10 3.70 dPas, 10 3.00 dPas~10 3.60 dPas, 10 3.10 dPas~10 3.60 dPas, 10 3.20 dPas~10 3.50 dPas, or 10 3.30 dPas~10 3.50 It may be in the range of dPas.
[0019] In a downdraw process, the vessel has an elongated nozzle from which the glass melt flows downward. The point at which the glass melt leaves the vessel is provided by an opening in the nozzle or by the end of a blade inserted into the nozzle, where the glass falls. In an overflow fusion process, this point is provided by the bottom side of the vessel, where the glass streams meet and merge to flow downward.
[0020] It is also advantageous if the viscosity increases sharply after emerging from the bath. The sharpness of the viscosity increase can be influenced by the choice of the glass composition and / or by applying a suitable cooling regime.
[0021] Detailed Description of the Invention Near-surface damage level (ONSL) describes the extent of superficial damage to the surface of a glass article. A "damage" is a volume having an extent of at least 1.0 μm that is not filled with glass but exists within the glass article as an open or closed cavity due to scratches, grooves, striae, gas inclusions, spalls, conchoidal fractures, and the like. The "extent" of a damage is its maximum diameter. The "extent" of a damage may also be referred to as the "length" of the damage. The "width" of a damage refers to the diameter of the damage in a direction perpendicular to the length of the damage. "Superficial" in this context means that the damage reaches the surface of the article at least in an area, or that they are at least in an area 1.0 μm or less below the surface. An area of the surface of a glass article is damage-free if it does not contain any damage, i.e., there is no damage at the surface and there is no damage at a depth of up to 1.0 μm below the surface.
[0022] ONSL can be specified as area coverage ONSL in %, where it is the area portion of the surface area considered that contains the damage. When ONSL is referred to in this disclosure, unless otherwise stated, ONSL is based on a specific size area area, typically 2×2 mm, not area coverage. 2 A numerical ONSL is meant which defines the number of near-surface defects based on an area of
[0023] The average ONSL in a particular area is determined by determining the number of near-surface defects in several different test areas and subsequently calculating the average value from this. The area of the area examined does not have to be identical to the area of the area defined as the basis for the ONSL. For example, if the ONSL is 2 x 2 mm 2 If the damage is determined based on the area of 2 × 2 mm, the number of near-surface damages is 2 In particular, the area of each test area and / or the total area of the test areas may be less than 2×2 mm 2 In an embodiment of the invention, the area of each test area can be, for example, at least 0.05 mm 2 , at least 0.1 mm2 , or at least 0.15 mm 2 The total area of the test area is, for example, at least 0.2 mm 2 , at least 0.5 mm 2 , at least 0.7 mm 2 , or at least 1.0 mm 2 In an embodiment of the invention, the test areas are arranged so as to be uniformly distributed. In particular, the individual test areas may be equally spaced from each other and / or from the edge of the glass article. For example, if four or nine test areas are inspected, they may be arranged in the shape of a square. In the case of nine test areas, naturally, the test area located in the center of the square does not have the same distance to the edge. The same distance to the edge applies in particular to the test areas located on the outside. The test areas can also be arranged in the shape of a rectangle or a circle. The shape of the arrangement of the test areas may in particular correspond to the shape of the two main sides. A substantially uniform distribution of the test areas is advantageous in particular for identifying representative ONSL.
[0024] The ONSL can be identified by microscopy, in particular with a magnification of 40x, preferably using a confocal laser scanning microscope, in particular a Zeiss LSM 800.
[0025] The calculation of the average ONSL is explained by an example. For a glass article of area 2×2 mm 2 For this purpose, several test areas, typically 2-10 (e.g. 7), may be used to determine the number of near-surface damages each. The area of each test area may be, for example, 0.1 mm 2 ~0.2mm 2 For example, each of 0.1 mm 2 If 10 test areas with an area of 1 mm are inspected and a total of 200 near-surface defects are detected overall, the average ONSL is 1 mm 2 or in other words, 2 × 2 mm 2 There are 800 pieces of damage in an area of 100m.
[0026] Alternatively or in addition to the average ONSL, the maximum level of damage near the surface (ONSL max For example, in the above example, if 40 near-surface defects are detected in one of the 10 test areas, and this number is the highest among all 10 test areas, then the ONSL max is the number of damages and ONSL max can be calculated as the product of the area content of the area region on which it is based and the quotient of the area content of the test area. Thus, in this example:
number
[0027] ONSL should be distinguished from surface roughness, which essentially describes smaller structures in the surface, the extent of which is significantly less than 1.0 μm. Exemplary roughness is typically less than 5 nm for polished / treated glass, and even lower for thermoformed surfaces. Glass articles, for example, can be particularly large, especially 2×2 mm 2 or 5×5mm 2 In an area of 100 mm, particularly preferably over the entire surface of one or both main sides of the glass article, the roughness R is less than 2 nm. a may have:
[0028] In particular, 2 x 2 mm 2 An average of less than 2000 ONSL damages, for example up to 1500, up to 1250, up to 1000, up to 750, up to 500, up to 400, up to 300, up to 200, up to 150, up to 125, up to 100, up to 90, up to 80, up to 70, up to 60, or up to 50, in an area area of 2×2 mm is advantageous. 2 The average ONSL in an area may be, for example, at least 1, at least 2, at least 5, at least 10, or at least 20 lesions.
[0029] In particular, 2 x 2 mm 2 ONSL in the area of maxAdvantageously, the number of lesions is up to 4000, for example up to 3000, up to 2500, up to 2000, up to 1500, up to 1000, up to 800, up to 600, up to 400, up to 300, up to 250, up to 200, up to 180, up to 160, up to 140, up to 120, or up to 100. 2 ONSL in the area of max may be, for example, at least 2, at least 4, at least 10, at least 20, or at least 40 lesions.
[0030] The glass article has a small thickness of less than 3.0 mm. In preferred embodiments, it is even significantly thinner, where in particular the article can have a thickness of less than 2.0 mm, less than 1.0 mm, or less than 500 μm. In certain embodiments, the article has a thickness of less than 350 μm, less than 250 μm, less than 150 μm, less than 100 μm, or even less than 50 μm. In particular, thin glass articles have the advantage that (besides the reduction in thickness as a contribution to miniaturization) they contribute only slightly to the weight of the pressure sensor. In particular in the automotive field or in portable electronic devices, low weight is important. However, very thin glass is also more difficult in terms of handling. For example, in the case of very thin glass, damage can occur very easily and the effort based on the tools required to handle very thin glass is high. In some embodiments, the thickness of the glass article is more than 5.0 μm, preferably even more than 10.0 or more than 20.0 μm. Particularly preferred glass articles of the invention have a thickness of more than 250 μm, for example at least 300 μm, at least 350 μm, at least 400 μm, at least 450 μm, or at least 500 μm. The thickness may, for example, be in the range of >250 μm to <3.0 mm, 300 μm to 2.75 mm, 350 μm to 2.5 mm, 400 μm to 2.25 mm, 450 μm to 2.0 mm, or 500 μm to 1.5 mm. The thickness may, for example, be up to 2.75 mm, up to 2.5 mm, up to 2.25 mm, up to 2.0 mm, up to 1.5 mm, or up to 1.0 mm.
[0031] The glass article is therefore preferably a flat item in the form of a plate, disk, wafer, sheet or the like. The article in particular has two main sides which have the greatest extent compared to the other sides of the article. The shortest distance between the two sides corresponds to the thickness of the glass article. The two main sides are in particular plane parallel.
[0032] Preferably, the ONSL described herein applies to at least the area of both major sides of the glass article. Where an ONSL is specified herein for an area of a glass article, this value preferably also applies to the corresponding area on the opposite major side of the glass article.
[0033] Portable technical devices are becoming smaller and smaller, requiring the highest possible packing or integration density. The same applies to automobiles, where the space available for pressure sensor modules and systems is becoming smaller and smaller (e.g. in-valve pressure sensors for measuring tire pressure). These trends drive the development towards smaller components. This also applies to pressure sensors. In order to obtain high measurement accuracy, in particular for the ONSL and / or ODS, a quality of the glass article needs to be achieved in an area that is sufficient for the production of the pressure sensor. Preferably, this area is less than 2×2 mm 2 Above, especially 4×4mm 2 For example, 5 x 5 mm 2 That's all.
[0034] The glass article itself can be significantly larger. Typically, the glass article is at least 100 mm 2 , at least 200 mm 2 , at least 400mm 2 , at least 600mm 2 , at least 800mm 2 , at least 2000mm 2 (Especially 2 inch (about 50 mm) diameter), at least 4400 mm 2 (especially 3 inches (approximately 75 mm) in diameter), and / or at least 74,000 mm2 (especially 12 inches (about 300 mm) in diameter). From such large glass articles, multiple components for making pressure sensors can be produced, for example by sawing (dicing) the components from the glass article. Larger or smaller sheets or wafers than those mentioned above can also be used. The glass article can have a rounded or angular bottom surface.
[0035] In a preferred embodiment, the glass article is at least 100 mm 2 , e.g. at least 200 mm 2 , at least 400mm 2 , at least 600mm 2 , at least 800mm 2 , at least 2000mm 2 (Especially 2 inch (about 50 mm) diameter), at least 4400 mm 2 (especially 3 inches (approximately 75 mm) in diameter), and / or at least 74,000 mm 2 (especially 12 inches (about 300 mm) in diameter). By "size" of the glass article is meant in particular the area coverage of one of both major sides of the glass article. In particular, both major sides of the glass article have the same area coverage.
[0036] In one embodiment, the glass article has a size of 2×2 mm, where the values described herein apply, particularly the ONSL and / or ODS. 2 The glass article may comprise at least 30 areal areas, in particular at least 40, or at least 45 areal areas having a size of 0.01 mm. Such glass articles are particularly suitable for economically manufacturing components for pressure sensors. In one embodiment, the areal portion of the glass article that satisfies the parameters ONSL and / or ODS is at least 50.0%, at least 60.0%, at least 70.0%, at least 80.0%, at least 90.0%, at least 95.0%, at least 98.0%, at least 99.0%, or at least 99.9% of the total area of the glass article. In one embodiment, the average ONSL and / or ONSL maxis substantially filled over the entire area of each of both major sides, particularly about 100% of the area of each of both major sides. In one embodiment, the ODS normalized to thickness avg , O.D.S. max and / or the ODS substantially fills the entire area of the glass article, in particular 100% of said area.
[0037] Positional thickness variation (ODS) describes the difference between the highest measured thickness, a, and the lowest measured thickness, b, within an area of a glass article. This includes: ODS i =a i - b i , where i = 1, 2, ..., n (n = the number of area regions of the glass article). max ) is the best ODS for this glass item i The minimum position and thickness variation (ODS) of the glass article min ) is the lowest ODS of this glass article i The average position-thickness variation (ODS) of the glass article avg ) is the ODS of this glass article i In this disclosure, ODS avg is often abbreviated and referred to as ODS. When ODS is referred to in this disclosure, unless otherwise specified, ODS avg means...
[0038] For the measurement, for example, an interferometer can be used, in particular a Precitec Sensor Interferometric-K interferometer. The sampling rate can in particular be 4 kHz. The scanning speed can in particular be 500 mm / sec. The distance between the measurement points can in particular be 0.125 mm.
[0039] The ODS is normalized to thickness and can therefore be specified based on the average thickness of the areal area considered, or the average thickness of the glass article, or the nominal thickness of the glass article. The deviation between the average thickness of the glass article and the nominal thickness of the glass article is usually negligible. Therefore, the nominal thickness is a good measure for the average thickness of the glass article and is preferably used for thickness normalization.
[0040] In particular, an ODS normalized to thickness of less than 10 nm per μm of thickness of the glass article is advantageous. An ODS normalized to thickness of less than 10 nm per μm of thickness of the glass article is preferably less than 2×2 mm 2 Areas of 4×4 mm or more 2 or even an area of 5×5 mm 2 This is achieved in an area of 2×2 mm or more. 2 The ODS normalized to thickness in an area of 5×5 mm is less than 5 nm / μm, or less than 2 nm / μm. 2 The ODS normalized to thickness in an area area of 2×2 mm is less than 5 nm / μm, or less than 2 nm / μm. Depending on the manufacturing method, certain ODS normalized to thickness cannot always be avoided, so the glass article in one embodiment has a thickness of 100 nm or less, particularly in an area area of 2×2 mm. 2 For example, 5 x 5 mm 2 For example, the present invention may have an ODS normalized to thickness of 0.001 nm / μm or more, such as at least 0.01 nm / μm, or at least 0.05 nm / μm, in an area area of 2×2 mm 2 The present invention relates to glass articles having an ODS normalized to thickness in the range of 0.001 to 10 nm / μm, 0.01 to 5 nm / μm, or 0.05 to 2 nm / μm in an area area of 5×5 mm. 2 The present invention also relates to a glass article having an ODS, normalized to thickness, in the range of 0.001 to 10 nm / μm, 0.01 to 5 nm / μm, or 0.05 to 2 nm / μm over an area area of 100 nm / μm.
[0041] ODS can also be specified without normalization to thickness, in which case the units "μm" are used, rather than "nm / μm" as in the case of thickness-normalized ODS. When no reference is made to normalization to thickness, it usually means ODS that is not normalized to thickness.
[0042] In one embodiment, the ODS is 2×2 mm 2 In one embodiment, the ODS has an area of 5×5 mm of less than 10 μm, in particular less than 5 μm, or less than 2 μm. 2 In one embodiment, the glass article has an area of less than 10 μm, in particular less than 5 μm, or less than 2 μm, depending on the manufacturing method, since certain ODS cannot always be avoided. 2 For example, 5 x 5 mm 2 For example, the present invention may have an ODS of 0.001 μm or more, such as 0.01 μm or more, particularly at least 0.05 μm, in an area area of 2×2 mm 2 The present invention relates to glass articles having an ODS in the range of 0.001 to 10 μm, 0.01 to 5 μm, or 0.05 to 2 μm in an area area of 5×5 mm. 2 The present invention also relates to a glass article having an ODS in the range of 0.001 to 10 μm, 0.01 to 5 μm, or 0.05 to 2 μm in an area of 10 μm.
[0043] In one embodiment, the maximum position-thickness variation (ODS) max ) is 2×2mm 2 In one embodiment, the ODS has an area of 5×5 mm of less than 50 μm, in particular less than 25 μm, or less than 10 μm. 2 In one embodiment, the glass article has an area of less than 2×2 mm, in particular less than 50 μm, in particular less than 25 μm, or less than 10 μm. Depending on the manufacturing method, certain ODS cannot always be avoided, so the glass article in one embodiment has an area of less than 2×2 mm 2 For example, 5 x 5 mm 2 In an area of 0.005 μm or more, for example 0.05 μm or more, in particular at least 0.25 μm, maxFor example, the present invention may have a 2×2 mm 2 ODS in the range of 0.005 to 50 μm, 0.05 to 25 μm, or 0.25 to 10 μm in the area area of max The present invention relates to a glass article having a size of 5×5 mm 2 ODS in the range of 0.005 to 50 μm, 0.05 to 25 μm, or 0.25 to 10 μm in the area area of max The present invention also relates to a glass article having the following structure:
[0044] The glass article should allow good, rapid and above all uniform thermal decoupling of the semiconductor and the medium to be measured in the pressure sensor. 2 Uniform thermal decoupling is achieved if the glass article in the above area exhibits a variation in thermal conductivity of 0.2 W / (m·K), in particular at room temperature, thus at a temperature in the range of 20° C. to 25° C., for example at 22° C., of not more than 0.15 W / (m·K), in particular at a maximum of 0.1 W / (m·K), in particular at a maximum of 0.05 W / (m·K), in particular at a maximum of 0.02 W / (m·K), or in particular at a maximum of 0.01 W / (m·K). Preferably, this value applies to the entire glass article. In this context, "variation" means the maximum difference in thermal conductivity, and thus the difference between the highest and lowest thermal conductivity in the corresponding area. In some embodiments, the variation in thermal conductivity may be, for example, at least 0.0001 W / (m·K), or at least 0.001 W / (m·K), in particular at room temperature, thus at a temperature in the range of 20° C. to 25° C., for example at 22° C. The thermal conductivity can be measured, for example, by the so-called laser flash method, which is based on ASTM E1461 and from the measured thermal diffusivity α, the specific heat capacity (C p ) and density (ρ) to calculate thermal conductivity (λ):
number
[0045] It is also possible to determine the thermal conductivity at a specific location of a glass article by calculation. In an undamaged location, the effective thermal conductivity λ effcorresponds to the thermal conductivity of glass λ. At the location where heat conduction occurs through the damage, the effective thermal conductivity can be calculated according to the following equation (2):
number
[0046] In equation (2), λ ガラス is the thermal conductivity of glass, and λ 空気 is the thermal conductivity of air, d is the thickness of the glass article, and Δx is the extent of the damage in the direction of heat conduction. In particular, heat conduction occurs from one of the major sides of the glass article, orthogonally through the glass article to the other major side of the glass article. 空気 is a suitable parameter for heat conduction through the damage, since the damage is the volume that is not filled with glass. At temperatures around room temperature, λ 空気 is approximately 0.0262 W / (m K), and is therefore significantly different from the typical thermal conductivity of glass, which is approximately 1.0 W / (m K) at the corresponding temperature. According to equation (2), for a glass article with a thickness d of 500 μm, a damage with an extent of Δx=1 μm in the direction of heat conduction already leads to a decrease in thermal conductivity of approximately 7%.
[0047] Temperature range: 20℃~300℃, 2.5~11×10 -6 / K, especially 3.0 to 9.5 × 10 -6 It has been shown to be advantageous when glass articles are used that have an average coefficient of thermal expansion (CTE) in the range of 1 / K. CTE is specified in accordance with DIN ISO 7991:1987.
[0048] Preferably, the glass article is 1 mm 3 Contains some gaseous inclusions less than 1.0 per square inch.
[0049] Viscosity-Temperature Profile The present invention is not limited to the fact that only glasses having a particular viscosity-temperature profile are suitable for the glass article of the present invention. However, it has been shown that a particular viscosity-temperature profile is advantageous. For particularly economical production, glasses that can be well manufactured in a draw process, such as the downdraw process or the overflow fusion process, are preferred, and therefore in particular glasses with a liquidus viscosity (above which crystals can form) of 10 3 dPas or more, preferably 10 3.5 More than 10 dPas, particularly preferably 10 4 Glasses can be formed having values above dPas.
[0050] It is particularly advantageous for reducing positional and thickness variations if the glass has a viscosity-temperature profile in which the viscosity is relatively high at the temperature at which the glass melt exits the bath in the downdraw of the overflow fusion process. It is further advantageous if the glass has a viscosity-temperature profile in which the increase in viscosity with decreasing temperature is relatively rapid. Any of the above measures, individually or in combination, will substantially reduce the susceptibility of the glass to developing substantial positional and thickness variations.
[0051] Usually, the Vogel-Fulcher-Tammann formula (VFT formula) is used to calculate the temperature required to achieve a certain viscosity of a glass (see also DIN ISO 7884-2:1998-2):
number
[0052] In the VFT equation, η is the viscosity, A and B are temperature-independent material parameters, T is the temperature, and T is the Vogel temperature. For a given glass, A, B, and T are constants.
[0053] Preferably, the glass has a value for B of at least 3500 K, at least 4000 K, or at least 4500 K. In particularly preferred embodiments, the glass has a value for B of at least 5000 K, at least 5500 K, or at least 6000 K. Preferably, B is at most 12000 K, at most 11000 K, at most 10500 K, at most 10000 K, at most 9500 K, or at most 9000 K. The parameter B may for example be in the range 3500-12000 K, 4000-11000 K, 4500-10500 K, 5000-10000 K, 5500-9500 K, or 6000-9000 K.
[0054] T0 is preferably at least 25° C., at least 50° C., at least 75° C., at least 100° C., or at least 120° C. Preferably, T0 is at most 300° C., at most 275° C., or at most 250° C., or at most 225° C., or at most 215° C. T0 may for example be in the range of 25° C. to 300° C., 50° C. to 275° C., 75° C. to 250° C., 100° C. to 225° C., or 120° C. to 215° C.
[0055] The value for A is preferably less than 0, less than -0.5, less than -0.75, less than -1.0, or less than -1.5. The value for A is preferably at least -5.5, at least -5.0, or at least -4.5. The value for A may be in the range of, for example, -5.5 to <0, -5.5 to <-0.5, -5.0 to <-0.75, -4.5 to <-1.0, or -4.5 to <-1.5.
[0056] Glasses having those VFT constants can be produced particularly well in a draw process, such as the downdraw process or the overflow fusion process.
[0057] Particularly preferably, the glass has the following VFT constants: A is in the range of -5.5 to <0.0, B is in the range of 3500 to 12000K, and / or T0 is in the range of 25°C to 300°C. Even more preferably, the glass has the following VFT constants: A is in the range of -5.0 to <-0.75, B is in the range of 4000 to 10000K, and / or T0 is in the range of 75°C to 270°C. Even more preferably, the glass has the following VFT constants: A is in the range of -4.5 to <-1.5, B is in the range of 4500 to 9000K, and / or T0 is in the range of 120°C to 250°C. Even more preferably, the glass has the following VFT constants: A is in the range of -4.5 to less than -1.5, B is in the range of 5000 to 10000K, and / or T0 is in the range of 100°C to 225°C. This is particularly advantageous for achieving a rapid increase in viscosity with decreasing temperature, so that the likelihood of developing substantial position and thickness variations is reduced.
[0058] The viscosity of the glass melt at the point where it leaves the bath is furthermore relevant. This viscosity is determined by two independent factors, on the one hand by the temperature at which the glass melt leaves the bath and on the other hand by the glass composition. The first factor is a process parameter that the skilled person can choose accordingly. For example, if the viscosity of the glass melt at the relevant point is too low, the skilled person can choose a reduced temperature to increase the viscosity. However, this can only be done rationally within certain limits. It is therefore advantageous if the glass has a composition such that the viscosity at the relevant temperature is relatively high. In particular, if the glass has a viscosity η10 according to the VFT formula at T=1400° C., the viscosity η10 according to the VFT formula at T=1400° C. is determined by the glass composition. 2.20 dPas or more, 10 2.30 dPas or more, 10 2.40 dPas or more, 10 2.50 dPas or more, 10 2.60 dPas or more, 10 2.70 dPas or more, 10 2.80 dPas or more, 10 2.90 dPas or more, 10 3.00 dPas or more, 10 3.10 dPas or more, 10 3.20dPas or more, or 10 3.30 It is advantageous if the viscosity η at T=1400° C. according to the VFT formula is, for example, up to 10 4.00 dPas, up to 10 3.90 dPas, up to 10 3.80 dPas, up to 10 3.70 dPas, up to 10 3.60 dPas, or up to 10 3.50 The viscosity η at T = 1400 ° C. according to the VFT formula is, for example, 10 2.20 dPas~10 4.00 dPas, 10 2.30 dPas~10 4.00 dPas, 10 2.40 dPas~10 3.90 dPas, 10 2.50 dPas~10 3.90 dPas, 10 2.60 dPas~10 3.80 dPas, 10 2.70 dPas~10 3.80 dPas, 10 2.80 dPas~10 3.70 dPas, 10 2.90 dPas~10 3.70 dPas, 10 3.00 dPas~10 3.60 dPas, 10 3.10 dPas~10 3.60 dPas, 10 3.20 dPas~10 3.50 dPas, or 10 3.30 dPas~10 3.50 It may be in the range of dPas.
[0059] In view of the VFT equation presented above, it can be seen that an increase in A, an increase in B, and / or an increase in T0 is associated with an increase in viscosity η at a given temperature T. However, increasing values of A and / or B are also associated with a less abrupt viscosity change in the relevant temperature range.
[0060] It is therefore advantageous if the components of the glass are selected in a balanced manner to obtain a desired viscosity-temperature profile, e.g., a component having a decreasing effect on a particular VFT constant is preferably balanced by a component having an increasing effect on the respective VFT constant or one of the other two VFT constants, or vice versa, to obtain an optimized viscosity-temperature profile.
[0061] The choice of glass constituents influences the temperature dependence of the refractive index. For example, the addition of SiO2 decreases the value A in the VFT formula and increases the values B and T0. The following table summarizes the influence of glass constituents on the VFT constants, where "+" denotes an increasing effect and "++" means that the value of the above mentioned constant is strongly increased. "-" denotes a decreasing effect and "--" means that the value of the considered constant is strongly decreased by increasing the amount of the glass constituent.
[0062] [Table 1]
[0063] Preferred glass composition The composition of the glass article is not limited to a particular glass. However, for particularly economical production, glasses that can be well manufactured in a draw process, such as the downdraw process or the overflow fusion process, are preferred. In one embodiment, the glass is a silicate glass, in particular a borosilicate glass or an aluminosilicate glass. Furthermore, keeping the glass composition within certain limits can be particularly advantageous for optimizing the viscosity-temperature profile so as to reduce the susceptibility of the glass to developing position-thickness variations. This is particularly true for glasses that have a relatively high viscosity at the point where the glass leaves the bath and / or have a rapid increase in viscosity with decreasing temperature.
[0064] With the help of glass composition, for example, the thermal conductivity (W / (m K)) and therefore the thermal transmittance (W / (m 2The thermal conductivity of the oxides can also be affected. Certain oxides, such as SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO or K2O, are associated with an increase in thermal conductivity. Other oxides, such as TiO2, Li2O or Na2O, are associated with a decrease in thermal conductivity.
[0065] In the present disclosure, the sum of the alkali metal oxides, particularly the sum of Li2O+Na2O+K2O, is also referred to as "R2O." Similarly, the sum of MgO+CaO+SrO+BaO+ZnO is also referred to as "RO."
[0066] In one embodiment, the glass comprises at least 60.0 mol% SiO2. Optionally, the content of SiO2 can be up to 87.0 mol%, or up to 85.0 mol%. Silicon dioxide contributes substantially to the durability of glass. However, it increases the processing temperature of glass, thus reducing the economics of production. In one embodiment, the glass comprises at least 67.0 mol%, or at least 75.0 mol%, more preferably at least 77.5 mol%, more preferably at least 80.0% mol% SiO2.
[0067] In some embodiments, the optional ingredient in the glass is B2O3.
[0068] For example, the glass may contain the following components in the proportions specified in mole percent: [Table 2]
[0069] It has been shown that glass articles comprising or produced from glasses comprising the following components in % by weight are particularly preferred in order to provide glass articles according to the embodiments and / or glass articles that can be produced in the methods according to the embodiments: Composition range 1: SiO260~65 B2O36~10.5 Al2O314~25 MgO 0~3 CaO 0~9 BaO 3~8 ZnO 0-2, The following applies here: the sum of the contents of MgO, CaO and BaO is characterized in being in the range of 8 to 18% by mass.
[0070] Composition range 2: SiO260~85 B2O35~20 Al2O32~15 Na2O 3~15 K2O 3~15 ZnO 0-12 TiO20.5~10 CaO 0~0.1.
[0071] Composition range 3: SiO275~85 B2O38~15 Al2O32~4.5 Na2O 1.5~5.5 K2O 0~2.
[0072] Composition range 4: SiO2 20-70, preferably 50-60, particularly preferably 52-58 B2O3 0.5-14, preferably 2-12, particularly preferably 2-4 Al2O3 15-41, preferably 16-24, particularly preferably 18-23 MgO 0.5 to 15, preferably 2 to 12, particularly preferably 3 to 5 CaO 0-5, preferably 0-3 BaO 0-7, preferably 0-6 ZnO 0 to 20, preferably 2 to 12, particularly preferably 8 to 10 Na2O 0-7, preferably 1-6, particularly preferably 3-5.
[0073] Composition range 5: SiO250~81 B2O30~5 Al2O30~5 R2O 5~28 RO 5~25 TiO2+ZrO20~6 P2O50~2.
[0074] Composition range 6: SiO252~66 B2O30~8 Al2O315~25 R2O 4~30 RO 0~6 TiO2+CeO20~2.5 ZrO20~2.5.
[0075] In all of the above-mentioned composition ranges, minor and / or trace components, e.g. in the form of coloring substances and / or fining agents, such as SnO2, CeO2, As2O3, Cl - , F - , sulfates may further be included.
[0076] In general, without being limited to the embodiments described herein, it may be advantageous if the glass has a morphology such that it is anodically bondable (or bondable). For this purpose, it may be advantageous if the glass contains a certain proportion of alkali and / or alkali oxides, in particular sodium and / or sodium oxide. In such an embodiment, the content of Na2O should be at least 0.5% by weight, but preferably not more than 6% by weight.
[0077] Furthermore, for the use of glass in pressure sensors, the average thermal expansion coefficient is relevant: 2.5 to 11×10 for the temperature range 20°C to 300°C. -6 / K, especially 3.0 to 9.5 × 10 -6 It has been shown to be advantageous to use glass articles having an average coefficient of thermal expansion (CTE) in the range of 3.1 to 3.3 ppm / K. The CTE is specified according to DIN ISO 7991:1987. In a particular embodiment of the invention, this is in the range of 3.1 to 3.3 ppm / K, which corresponds to the coefficient of expansion of silicon.
[0078] In the best case, for all temperatures in the temperature interval 20-400°C, the relative change in length ΔL / L is similar to the progression of silicon, and in the best case, it is identical.
[0079] Manufacturing method The glass articles of the present invention can be manufactured, for example, by a draw process. Exemplary draw processes are downdraw, overflow fusion, and redraw. Downdraw and / or overflow fusion are particularly preferred.
[0080] Depending on the quality of the surface, post-treatment may be required. Exemplary post-treatment steps are polishing, grinding and lapping. Grinding and optionally subsequent polishing are particularly advantageous. Grinding with bonded abrasives, especially with diamond abrasives, is particularly preferred.
[0081] Typically, using the drawing process, glass articles are obtained that are already characterized by a very good near-surface damage level. However, unless further targeted measures are taken, the drawn glass may have a high ODS. Glass articles that are not drawn but are produced as ingots in a casting process and subsequently sawed and polished often have a very low ODS but a high degree of near-surface damage. In the method according to the invention, measures are taken to provide glasses that are characterized by both a low ODS and a low ONSL and are therefore particularly well suited as components in pressure sensors. The method described below is also advantageous from an economic point of view, since it can be operated in a continuous manner.
[0082] In one embodiment, the present invention is a method for manufacturing a glass article, comprising the steps of: producing a glass melt, - fining the glass melt; drawing the glass melt, in particular using drawing rolls, into a glass ribbon having a target thickness in the range of less than 3.0 mm, dividing the glass ribbon into glass articles. The glass ribbon passes through a region Z where the glass ribbon has already achieved a target thickness, but its viscosity is still 10 10 is less than dPas, the glass is drawn in the zone Z at a drawing speed of at least 0.5 m / min and at most 50 m / min, for example 2 to 10 m / min, 10 to 25 m / min, or 25 to 50 m / min; and wherein appropriate measures are taken to keep the region Z free from interference effects in the frequency range of 0.01-500 Hz, e.g. 0.05-400 Hz, 0.1-300 Hz, 0.5-250 Hz, 0.8-200 Hz, 1-100 Hz, 4-75 Hz, or 5-50 Hz.
[0083] In particular, it has been found that frequencies above 1 Hz are associated with the appearance of relevant position-thickness variations. Therefore, suitable measures should be taken to keep the area Z free from interference effects in the frequency ranges 1-500 Hz, 2-400 Hz, 3-300 Hz, 4-250 Hz, 5-200 Hz, 10-100 Hz, 15-75 Hz, or 20-50 Hz. For example, suitable measures may be taken to keep the area Z free from interference effects having frequencies of at least 1 Hz, at least 2 Hz, at least 3 Hz, at least 4 Hz, at least 5 Hz, at least 10 Hz, at least 15 Hz, or at least 20 Hz. For example, suitable measures may be taken to keep the area Z free from interference effects having frequencies of up to 500 Hz, up to 400 Hz, up to 300 Hz, up to 250 Hz, up to 200 Hz, up to 100 Hz, up to 75 Hz, or up to 50 Hz.
[0084] The interference effects in the abovementioned frequency range can be achieved, for example, by an acoustic housing in the drawing facility and / or in the area Z. Optionally, the interference effects in the facility can already be minimized by adjusting the distance of the drawing rolls (especially in the drawing direction).
[0085] In this way, the natural vibrations of the glass can be suppressed. The natural vibrations of the glass occur in particular at the natural frequency EF of the glass as well as at its multiples (frequency f=n×EF). By appropriately arranging the drawing rolls or rollers, their natural vibrations can be suppressed. For example, a second drawing roll can be arranged between the first drawing roll and the HFG zone (hot forming zone) such that the distance of the second drawing roll to the first drawing roll is selected to be less than 1 / n of the distance of the first drawing roll to the HFG zone, thereby suppressing the natural vibrations with n×EF.
[0086] The relevant natural frequencies can be evaluated, for example, if the glass ribbon is considered as a string, according to the following formula:
number
[0087] where L is the string length, Ψ is the tension, and μ is the mass coverage. If the glass ribbon is considered as a two-dimensional object (a membrane instead of a string), further natural frequencies can be identified.
[0088] In order to minimise the effects of interference, vibration decoupling can be provided, particularly in the range of 0.01-500 Hz, e.g. 0.05-400 Hz, 0.1-300 Hz, 0.5-250 Hz, 0.8-200 Hz, 1-100 Hz, 4-75 Hz or 5-50 Hz, or in the frequency range of 1-500 Hz, 2-400 Hz, 3-300 Hz, 4-250 Hz, 5-200 Hz, 10-100 Hz, 15-75 Hz or 20-50 Hz.
[0089] It may be advantageous to exclude certain frequency ranges and / or create a detuning relative to the natural frequency.
[0090] It is also advantageous to moderate the convection in the cooling area to prevent the glass from vibrating. This can be achieved, for example, with the aid of panels (shielding of the pressure cascade). A seal, in particular an airtight seal, may also be provided.
[0091] Also, if the drawing equipment and the molding are separated, vibrations can be avoided, and therefore the transmission of vibrations to the molding can be prevented.
[0092] The drawing of the glass melt may involve, inter alia, downdraw or overflow fusion. In both cases, the glass melt emerges from the bath and is then drawn into a glass ribbon. The viscosity that the glass melt has at the point where it emerges from the bath is particularly relevant to the appearance of position and thickness variations. In particular, for the glass melt to be drawn properly, the viscosity must be greater than 10 4 However, if the viscosity is too low, the glass ribbon will be too long in the viscosity range which will tend to cause position and thickness variations during drawing. Therefore, the viscosity of the glass melt at the point where it leaves the bath should be less than 10 2.20 dPas or more, 10 2.30 dPas or more, 10 2.40 dPas or more, 10 2.50 dPas or more, 10 2.60 dPas or more, 10 2.70 dPas or more, 10 2.80 dPas or more, 10 2.90 dPas or more, 10 3.00 dPas or more, 10 3.10 dPas or more, 10 3.20 dPas or more, or 10 3.30 The viscosity of the glass melt at the point where it leaves the vessel should be, for example, up to 10 4.00 dPas, up to 10 3.90 dPas, up to 10 3.80 dPas, up to 10 3.70 dPas, up to 10 3.60 dPas, or up to 10 3.50 The viscosity of the glass melt at the point where it leaves the vessel may be, for example, 10 2.20 dPas~10 4.00 dPas, 10 2.30 dPas~10 4.00 dPas, 10 2.40 dPas~10 3.90 dPas, 10 2.50dPas~10 3.90 dPas, 10 2.60 dPas~10 3.80 dPas, 10 2.70 dPas~10 3.80 dPas, 10 2.80 dPas~10 3.70 dPas, 10 2.90 dPas~10 3.70 dPas, 10 3.00 dPas~10 3.60 dPas, 10 3.10 dPas~10 3.60 dPas, 10 3.20 dPas~10 3.50 dPas, or 10 3.30 dPas~10 3.50 It may be in the range of dPas.
[0093] The viscosity of the glass melt at the point of exiting the vessel is determined primarily by two independent factors, on the one hand by the temperature at which the glass melt exits the vessel and on the other hand by the glass composition. The first factor is a process parameter that the skilled person can select accordingly. For example, if the viscosity of the glass melt at the relevant point is too low, the skilled person can select a reduced temperature to increase the viscosity.
[0094] It is also advantageous if the viscosity increases sharply after emerging from the bath. The sharpness of the viscosity increase can be influenced by the choice of the glass composition and / or by applying a suitable cooling regime.
[0095] Advantageous Embodiments In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 the glass article having an average near-surface damage level (ONSL) of less than 2000 defects having an extent of at least 1.0 μm.
[0096] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2The glass article has an average position-thickness variation (ODS) normalized to the thickness at 100 nm per 1 μm of thickness.
[0097] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, an ODS of 2×2 mm 2 or 5×5mm 2 The glass article has an area of less than 10 μm.
[0098] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, comprising an ONSL max is 2×2mm 2 The glass article has up to 4000 particles in an area of 100 mm.
[0099] In one aspect, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article having an ODS of less than 3.0 mm. max ) is 2 x 2 mm 2 or 5×5mm 2 The glass article has an area of less than 50 μm.
[0100] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm and a thermal conductivity variation of less than 2×2 mm 2 the thermal conductivity of the glass article is 0.2 W / (m K) or less per area.
[0101] In one aspect, the present invention relates to a glass article having a thickness of less than 3.0 mm, said glass article having a viscosity-temperature profile characterized by the following VFT parameters: A in the range of -5.5 to <0.0, B in the range of 3500 to 12000 K, and / or T0 in the range of 25°C to 300°C.
[0102] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2The average damage level near the surface (ONSL) is less than 2000 damages having an extension of at least 1.0 μm, and the ODS is less than 2 × 2 mm 2 The glass article has an area of less than 10 μm.
[0103] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 The average damage level near the surface (ONSL) at the max ) but 2×2mm 2 The glass article has an area of less than 50 μm.
[0104] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 The average damage level near the surface (ONSL) in the specimen is less than 2000 damages with a spread of at least 1.0 μm, and the thermal conductivity variation is less than 2 × 2 mm 2 the thermal conductivity of the glass article is 0.2 W / (m K) or less per area.
[0105] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 the average damage level near the surface (ONSL) at 2000 or less damages having an extent of at least 1.0 μm, and the viscosity-temperature profile is characterized by the following VFT parameters: A is in the range of -5.5 to <0.0, B is in the range of 3500 to 12000 K, and / or T0 is in the range of 25°C to 300°C.
[0106] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 The average thickness-normalized position-thickness variation (ODS) at the ONSL is less than 10 nm per μm of thickness. max But 2×2mm2 The glass article has up to 4000 particles in an area of 100 mm.
[0107] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 The average thickness-normalized position-distance variation (ODS) at 2 × 2 mm is less than 10 nm per μm of thickness, and the thermal conductivity variation is less than 2 × 2 mm. 2 the thermal conductivity of the glass article is 0.2 W / (m K) or less per area.
[0108] In one embodiment, the present invention provides a glass article having a thickness of less than 3.0 mm, the glass article being 2×2 mm 2 the average position-thickness variation (ODS) normalized to thickness at is less than 10 nm per μm of thickness, and the following VFT parameters: A is in the range of -5.5 to <0.0, B is in the range of 3500 to 12000 K, and / or T0 is in the range of 25°C to 300°C. [Brief description of the drawings]
[0109] [Figure 1] FIG. 1 illustrates an exemplary pressure sensor. [Diagram 2] FIG. 13 is a side view of near-surface damage. [Diagram 3] FIG. 1 shows an exemplary image of a sample according to Example 1. [Figure 4A] FIG. 1 is a box plot of the ODSi distribution normalized with respect to the nominal thickness d for an areal area (2×2) mm2 for glass articles produced in a downdraw process. [Figure 4B] FIG. 1 is a box plot of the ODSi distribution normalized with respect to the nominal thickness d for an areal area (5×5) mm2 for glass articles produced in a downdraw process. EXAMPLES
[0110] The invention will now be described in more detail with the aid of the following examples.
[0111] 1. Example 1 The glass articles were subjected to various post-treatment steps. Example 1A was post-treated by lapping and polishing. Example 1B was post-treated by grinding and polishing. In detail, the post-treatment protocol was as follows:
[0112] [Table 3]
[0113] The same polishing step was carried out in Examples 1A and 1B. The only difference between both examples is that Example 1A was subjected to lapping as described above, whereas Example 1B was subjected to grinding as described above.
[0114] The effect of different post-treatment steps on the near-surface damage level (ONSL) was observed under a microscope (Zeiss LSM 800) at 40x magnification with 65% illumination at 120V. An exemplary image is shown in Figure 3. Each black dot was interpreted as one damage. To avoid counting errors due to contamination adhering on the surface, the surfaces of the samples were cleaned before evaluation under the microscope.
[0115] The results are summarized in the table below, where ONSL denotes the average number of near-surface damage in a given area, respectively: For each of Examples 1A and 1B, seven specimens were examined each.
[0116] [Table 4]
[0117] A comparison of Examples 1A and 1B shows that grinding achieves better results (lower degree of ONSL) than lapping.
[0118] The nominal thicknesses of Examples 1A and 1B after appropriate post-processing were each in the range of about 400 μm to about 450 μm. 2 and 5×5mm 2 The location-thickness variation (ODS) was determined for the area area. No difference in relation to the ODS values was found between Examples 1A and 1B.
[0119] 2×2mm 2 For an area of 100m2, the individual ODSs of Examples 1A and 1B are i The average position-thickness variation (ODS) was determined as the arithmetic mean of the values avg ) were each about 0.05 μm. 2 The ODS per nominal thickness in the area ranged from 0.11 to 0.13 nm / μm.
[0120] 5×5mm 2 For an area of 100m2, the individual ODSs of Examples 1A and 1B are i The average position-thickness variation (ODS) was determined as the arithmetic mean of the values avg ) were approximately 0.13-0.14 μm, respectively. 2 The ODS per nominal thickness in the area ranged from 0.27 to 0.34 nm / μm.
[0121] 2. Example 2 Glass articles having a nominal thickness of 700 μm or 250 μm were produced by a downdraw process, each having a length of 510 mm and a width of 430 mm.
[0122] The actual location-dependent thickness of a glass article was determined optically using interferometry, whereby light is focused onto the glass article and interference resulting from differences in the paths of reflection on the front and back sides of the article is used to determine the local thickness of the glass article.
[0123] For the measurements, a Precitec Sensor Interferometric-K interferometer was used. The sampling rate was 4 kHz. The scanning speed was 500 mm / s. The measurement point spacing was 0.125 mm.
[0124] The measurement tracks were measured in a direction perpendicular to the glass-pulled direction. The distance between the two measurement tracks was 10 mm. Therefore, the measured spatial resolution in the glass-pulled direction was only 10 mm. To increase the resolution in the pull-out direction, a linear interpolation was performed. As a result, the spatial resolution in the glass-pulled direction could be increased to 1 mm. The error introduced by the interpolation was estimated to be <0.05 μm. Therefore, the interpolation does not lead to any relevant result deviations.
[0125] Based on the thickness value so obtained, 2 x 2 mm 2 and 5×5mm 2 The location and thickness variation (ODS) was determined for area areas of 2 × 2 mm. The area areas were selected such that one of the measurement points was always in the center of one area. Thus, for each measurement point, one area was calculated and evaluated for ODS. The location was too close to the edge of the glass article and was 2 × 2 mm. 2 and 5×5mm 2 The only exceptions were measurement points that did not serve as the center of an areal area. With a positional resolution of 1 mm each in the direction of pulling the glass article and in the direction perpendicular to the pulling direction, this results in approximately 200,000 evaluated areal areas per glass article.
[0126] Four glass articles (e.g. "V1") with a nominal thickness of 250 μm were examined from different test series (hereinafter referred to as V1 to V6). Furthermore, ten glass articles (e.g. "V2 to V6") with a nominal thickness of d=700 μm were examined (two glass articles each per test). (2×2) mm 2 The number of area areas considered using is 204,408 per glass article, which is (5×5) mm 2The number of area regions considered using was 202,905 per glass article.
[0127] Interestingly, it was found that for the 700 μm nominal thickness, the identified ODS values did not vary within a test, but varied significantly between tests (V2–V6). However, for the 250 μm nominal thickness, no relevant deviations were found in terms of ODS values for the different specimens. Therefore, in the following, for the 250 μm nominal thickness, only one ODS value is specified, while for the 700 μm nominal thickness, its upper and lower limits are respectively the highest and lowest ODS values of the examined specimens of all tests. avg Specifies the range of values that correspond to the value.
[0128] The ODS values shown are each individual ODS i The average position-thickness variation (ODS) was determined as the arithmetic mean of the values avg ) (2×2)mm 2 For an area of , the ODS is 204,408 ODS i The average value is calculated as (5×5) mm. 2 For each area, the ODS is 202,905 ODS per test. i It is the average value of the values.
[0129] The results are summarized in the following table: [Table 5]
[0130] The data on which the above summary is based are expressed as ODS per nominal thickness d. i The values are shown in the form of a box plot in FIG. 4, where FIG. 4A shows the area of (2×2) mm 2 Regarding FIG. 4B, the area is (5×5) mm 2 Regarding.
[0131] Description of the drawings FIG. 1 shows an exemplary pressure sensor diagrammatically, but not to scale. The pressure sensor is shown in cross section and comprises a base 60, which may be made, for example, of a ceramic material. On the base 60 a glass element 100 is fixed with an adhesive layer 63, for example made of epoxy resin. The glass element 100 comprises an opening. The pressure sensor comprises a MEMS chip 61 made of silicon as a central sensitive unit. In its central region it comprises a thinned portion (filament). The piezoresistive function is integrated in this filament. The MEMS chip 61 is anodically bonded to the glass element, forming a measurement cavity 600. A reference pressure cavity 601 is formed by a locally thinned portion 62. This component can be made either from silicon or glass and is hermetically connected to the MEMS chip 61, for example by anodic bonding or heat fusion.
[0132] Figure 2 shows a side view of the near-surface damage at 1000x resolution.
[0133] Figure 3 shows exemplary images of samples from Example 1 for analysis of near-surface damage level (ONSL) at 40x magnification. Figures 3A and 3B correspond to samples from Examples 1A and 1B, respectively. It can be seen that the ONSL in Example 1A (Figure 3A) is higher than that in Example 1B (Figure 3B).
[0134] FIG. 4 shows the area (2×2) mm of a glass article produced by the downdraw method. 2 (Figure 4A) and (5 × 5) mm 2 For (Figure 4B), ODS normalized with respect to the nominal thickness d at nominal thicknesses of 250 μm (V1) and 700 μm (V2–V6) i Shown is a box plot of the distribution. Each box is bounded by a lower and upper quartile. The median is shown as a horizontal line within the box. The mean is shown as a horizontal line extending beyond the horizontal limits of the box.
Claims
1. 1. A glass article having two parallel planar major sides, said glass article having a thickness of less than 3.0 mm, said glass article having a thickness of less than 2.0 mm on each of said major sides, said thickness being less than 2.0 mm. 2 The glass article has an average near-surface damage level (ONSL) of less than 2000 damages having an extent of at least 1.0 μm, and the glass article has a size of 2×2 mm 2 The average thickness-normalized deviation (ODS) at 2×2 mm is less than 10 nm per μm of thickness of the glass article. 2 The difference between the highest thickness and the lowest thickness within a specified measurement area of the glass article.
2. 2 x 2 mm 2 2. The glass article of claim 1, wherein the average positional thickness variation in the glass article is less than 10 μm.
3. 2 x 2 mm 2 Maximum position and thickness variation (ODS max 3. The glass article of claim 1, wherein the thickness of the glass is less than 50 μm.
4. said glass article having a thickness of 2×2 mm on both major sides; 2 Maximum near-surface damage level ONSL max The glass article according to any one of claims 1 to 3, wherein the number of damages is up to 4000, each having an extent of at least 1.0 μm.
5. 5. The glass article of any one of claims 1 to 4, having a thickness of less than 2.0 mm, less than 1.0 mm, or less than 0.5 mm.
6. 2 x 2 mm 2 Roughness R of less than 2 nm a The glass article according to any one of claims 1 to 5, having
7. The number of gaseous inclusions is 1 mm 3 7. The glass article of claim 1, wherein the average particle size is less than 1.0 per square meter.
8. The following VFT parameters: A is in the range of -5.5 to <0.0, B is in the range of 3500 to 12000 K, and / or T 0 The glass article according to any one of claims 1 to 7, which is made of glass having a viscosity-temperature profile characterized in that
9. 2 x 2 mm 2 9. The glass article according to claim 1, wherein the maximum difference in thermal conductivity at is at most 0.2 W / (m·K).
10. At least 400 mm 2 10. The glass article of claim 1 having an area of
11. Area 1-10mm 2 , preferably 3 to 6 mm 2 , in particular about 2×2 mm 2 A glass article according to any one of claims 1 to 10, in particular a glass article producible by dividing a glass article according to any one of claims 1 to 10.
12. 12. Use of a glass article according to claim 11 in a pressure sensor, in particular as a component of a pressure sensor.
13. A pressure sensor comprising the glass article of claim 11.
14. A method for producing a glass article, in particular a glass article according to any one of claims 1 to 11, comprising the following steps: - producing a glass melt; - fining the glass melt; drawing the glass melt into a glass ribbon having a target thickness in the range of less than 3.0 mm, in particular using drawing rolls; dividing the glass ribbon into glass articles; The glass ribbon passes through a region Z, where the glass ribbon has already achieved a target thickness, but its viscosity is still 10 10 less than dPas, the glass is drawn in zone Z at a drawing speed of at least 0.5 m / min and at most 50 m / min; and The method, wherein appropriate measures are taken to keep said region Z free from interference effects in the frequency range 0.01 to 500 Hz.
15. A method according to claim 14, in which appropriate measures are taken to keep said area Z free from interference effects in the frequency range 1 to 500 Hz.
16. 15. The method of claim 14, wherein the method is a downdraw process or an overflow fusion process.
17. The glass melt exits the vessel and is then drawn into a glass ribbon, where the viscosity of the glass melt at the point where it exits the vessel is 10 2.20 dPas to 10 4.00 17. The method of claim 16, wherein the viscosity is in the range of dPas.
18. The means comprises: the extraction facility and / or the acoustic housing of the area Z, - Separation of drawing equipment from molding, - Adjustment of the pull-out roll distance One or more panels to reduce convection, especially in the cooling area Sealing, and ・ Combinations of these 18. The method according to any one of claims 14 to 17, wherein the compound is selected from the group consisting of
19. The following steps: grinding the glass article with a bonded abrasive, in particular with a diamond abrasive; - a subsequent optional polishing step; 19. The method of any one of claims 14 to 18, comprising: